Indoor Air Pollution - Smith, Kirk R. (World Bank, Washington, DC, 2012)
Outdoor air pollution in developing-country cities is difficult to overlook. Indoor air pollution caused by burning such traditional fuels as wood, crop residues, and dung is less evident, yet it is responsible for a significant part of country and global disease burdens. The main groups affected are poor women and children in rural areas and urban slums as they go about their daily activities. This note reviews the evidence on health effects from indoor air pollution in developing countries, looking in detail at India. It outlines possible solutions and concludes that the only feasible long-term remedy is improved access to cleaner modern energy.